1996
DOI: 10.1161/01.cir.94.4.708
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Association of the Deletion Allele of the Angiotensin-Converting Enzyme Gene With Myocardial Infarction

Abstract: Within the limitations of the available data, the meta-analysis therefore supports an association of the ACE D allele with MI risk and strengthens the justification for further evaluation in appropriately powered studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
216
4
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(247 citation statements)
references
References 24 publications
21
216
4
6
Order By: Relevance
“…3, basal ACE activity of the participants showed a significant difference between the ACE II genotype and the ID and DD genotypes in accordance with the results of Rigat et al (22) . The D allele of the ACE gene was previously proposed to be correlated with CVD (26,36) . According to Fig.…”
Section: Discussionmentioning
confidence: 98%
“…3, basal ACE activity of the participants showed a significant difference between the ACE II genotype and the ID and DD genotypes in accordance with the results of Rigat et al (22) . The D allele of the ACE gene was previously proposed to be correlated with CVD (26,36) . According to Fig.…”
Section: Discussionmentioning
confidence: 98%
“…23,24 In the general population, the ACE I/D D allele has been related to cardiovascular mortality in several meta-analyses, although such association was not duplicated by others. [25][26][27] Our recent studies found that patients with the ACE I/D gene D allele and AT1R gene A1166C C allele in RAS genes were more likely to develop DHF. 28,29 In this study, we demonstrated that the ACE I/D gene D allele and AT1R gene A1166C C allele were associated not only with the development of DHF but also with the long-term prognosis.…”
Section: Survival Free Of Death From Cardiovascular Eventsmentioning
confidence: 94%
“…The frequency of ACE DD genotype has been reported to be increased in patients with MI [38], dilated cardiomyopathy, and SCD [38][39][40]. Although one recent study showed that HF patients carrying the DD genotype were more likely to die from progressive pump failure rather than SCD, the differential use of ACE inhibitors in the two groups (i.…”
Section: Renin-angiotensin-aldosterone (Raas) Cascadementioning
confidence: 99%